Pengaruh Pengetahuan Keuangan, Sikap Keuangan Dan Kepribadian Terhadap Perilaku Manajeman Keuangan Pada Pelaku Umkm Penghasil Susu Di Pujon (Studi Kasus Pada Koperasi Susu Sae Pujon) - Ulfa Baddrin Afdilla; Budi Wahono; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis research was conducted at SAE Milk Cooperative Pujon Malang. This type of research is qualitative research (quantitative research). The purpose of this study was to determine the effect of financial knowledge, financial attitudes and personality on financial management behavior on milk-producing MSMEs in Pujon. The independent variables used are financial knowledge, financial attitudes, and personality. while the dependent variable is the behavior of financial management. The sample used in this study were 60 respondents who were MSME players in the SAE Pujon milk cooperative. The data collection technique used a questionnaire. The analytical method used is the instrument test, reliability test, normality test, classic assumption test, multicollierity test, heteroscedasticity test, multiple linear regression test, f test and t test using the help of SPSS 25 computer software data processing. The results of this study indicate that financial knowledge has a significant positive effect on financial management behavior, financial attitudes have a significant positive effect on financial management behavior, personality has a significant positive effect on financial management behavior.(Keyword : Financial Knowlagde, Financial Attitude, and Personality)